TEACHING L2 VOCABULARY THROUGH LOGIC PUZZLES - McDonald, Kurtis (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This article presents the idea of using logic puzzles as a task-based teaching technique in foreign language classrooms to foster second language vocabulary acquisition. The general advantages of using logic puzzles are that they can be both mentally challenging and fun for students while producing numerous pedagogical benefits. These benefits are believed to include an increased exposure to vocabulary presented in specific contexts with a distinct focus on comprehending meaning, a heightened mental engagement with the key vocabulary at a deep level of processing, and the fostering of inference skills and the ability to guess meaning from context, all in a relatively brief amount of class time. Furthermore, logic puzzles offer a great deal of adaptability in exactly how they are utilized in class. Ultimately, it can be concluded that logic puzzles should be explored more thoroughly for their potential benefits to classroom teaching and the learning of foreign languages through continued use and more substantial research studies. Resumen Este artículo presenta el uso de problemas de lógica como una técnica de enseñanza de lenguas extranjeras a base de tareas, para fomentar la adquisición de vocabulario. Las ventajas generales de los problemas de lógica incluyen el hecho de que son desafíos mentales y también el hecho de que son tareas divertidas para los alumnos, al mismo tiempo que se obtienen beneficios pedagógicos. Estos beneficios incluyen una alta exposición a un vocabulario presentado en contextos específicos y con un énfasis en la compresión de significado; su valor como actividad en la que el estudiante tiene que procesar el vocabulario a un nivel profundo y utilizar la habilidad mental de inferir el significado a través del contexto; y todo esto en un tiempo relativamente breve. Además, los problemas de lógica son muy flexibles con respecto a cómo se utilizan en clase. Para terminar, se puede concluir que la utilización de problemas de lógica y sus beneficios potenciales en la enseñanza y adquisición de lenguas extranjeras merecen una investigación continuada y más profunda.